Buckling and post-buckling characteristics of axially loaded channel-section CFRP/aluminum laminate profiles under the influence of impact damage. (February 2023) - Zhang, Fukai; Lin, Yuan; Zhang, Zhongwei; Song, Chunming; Huang, Yaxin; Wang, Mingyang
Abstract: Damage caused by random impact incidents can greatly reduce the load bearing capacity of composite structural components. In this study, numerical simulations were performed to investigate the influence of impact damage on the buckling and post-buckling performance of carbon fiber reinforced polymer (CFRP)/aluminum laminate (CARALL) channel-section profiles. Low-velocity impact experiments and simulations were performed first on CARALL panel with the exact stacking configuration of the profiles to characterize the possible failure mechanisms for such hybrid components. Then, the dynamic responses of the channel-section profiles with the corner, web and flange impacted respectively, and the corresponding residual properties under axial compression were numerically revealed. Results showed that the residual deformation of specimens after impact was the dominate factor concerning its residual buckling load, and the post-buckling strength was mainly determined by the material damage propagation in the post-buckling stage. The specimens with corner impacted exhibited the highest residual axial buckling load and the lowest failure load compared with the ones with web or flange impacted. This work intended to provide insight into developing novel fiber reinforced polymer/metal hybrid structural components with high impact resistance. Highlights: 3D progressive damage model based on the Hashin and Puck criterion was proposed and used in the simulation. The Effects of impact locations on the low-velocity impact behavior was analyzed through simulation. The residual compressive behavior and damage propagation features of the pre-impacted profiles were discussed.